(untitled) (Research, Society and Development, 2022)
The main objective of this research was to analyze the elements of the value chain based on the Theory of Change in the context of an organization in the city of Maceió, in the state of Alagoas. The research started from the importance of identify and characterize the Theory of Change value chain in a social enterprise in the impact assessment process. In order to reach these objectives, it was decided to analyze each element of the value chain individually within the scope of the studied enterprise. As for the methodology, a qualitative approach was chosen, based on an interview via Skype with the company’s CEO. The content analysis method was used, applied in a case study strategy. The research was characterized as descriptive, depending on the objective. It was observed that, despite the challenges inherent to social business, the company has taken its first steps in relation to monitoring and impact assessment and that the generation of impact is configured as a company commitment. Thus, from the construction of the company’s theory of change, this tool can be used to measure its performance and have greater ease in its decision-making processes.